Evaluation of Science Implementation in Mechanical Engineering Design Curriculum Class 2A State Polytechnic of Jakarta Pekalongan City Campus Academic Year 2023/2024 - Dewadi, Fathan Mubina; Supriyadi, Supriyadi; Sulaiman, Abel Raffi Putra; Ulhakim, Muhamad Taufik (YCMM, 2024)
The influence of science in mechanical engineering design is very significant. Science provides a foundation of in-depth knowledge of the principles of physics, mathematics, and chemistry that are used to design efficient and innovative machines. The method used is a quantitative method with descriptive statistics. This method is an approach to research that focuses on data collection and data analysis based on numbers or quantities. From the method presented, it can be concluded that this method can make it easier to make better decisions based on structured numerical information. The results of this research refer to 3 parameters, namely kurtosis value, maximum value and minimum value. several other parameters are also displayed such as mean value, standard error, median, mode, standard deviation, sample variance, skewness, range, sum and count. It can be concluded from this study that the data does not have a normal distribution because the kurtosis number is not 0. Based on the data descriptive statistics, the maximum valuein this study is 31, the minimum value in this study is 20.